Development of Numerical Code for Two Dimensional Dispersion Flow - Rifqi - Nim: 13614026, Ahmad
The release of matter (toxic substances) into the atmosphere, whether by intent or accident, can cause serious harm to humans and the surrounding environment. Materials that have been released into the atmosphere can be easily detected using existing sensor equipment today. However, a precaution is needed to minimize the number of casualties and losses that occur. This study aims to develop a software to analyze the dispersion of the substances. The analysis will be performed at the highest risk area, after the analysis has been done, the next analysis will be performed for mitigation purpose. In this study, the developed software will use Finite Volume Method (FVM) and Upwind method as the main discretization technique. The software development will be focused on the early stage of software development. The results will be compared to OpenFOAM for the velocity field and also analytics results for the dispersion case. The software results are very comparable to the results from the control case(analytics and commercial software).